The Development of Oro-Oro Dowo Traditional Market Logistics in the New Normal Era with Joint Delivery Approach - Riza Nuansyah Putra; Ismu Rini Dwi Ari; Christia Meidiana (Eduvest - Journal of Universal Studies, 2022)
The growth of electronic commerce is one of the challenges for the development of urban logistics in Indonesia. This condition was then exacerbated by the COVID-19 pandemic, which forced changes to the social interaction system. In Malang City in particular, there are regulations that make traditional markets prioritize electronic purchasing systems. Oro-oro Dowo Market is supported by 4 service developers who support online transaction activities. Each development has its own mechanism for the movement of goods according to the characteristics of the service developer. Using a qualitative descriptive method, it is known that additional traditional market facilities are needed to support these activities. The spatial arrangement of the Oro-oro Dowo Market is an initial alternative for developing a development strategy. Then the concept of online traditional market interaction patterns can be considered for the development of other digital-based activities.